1996
DOI: 10.1093/infdis/174.1.120
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nitric Oxide in Bacterial Meningitis in Children

Abstract: To investigate the role of nitric oxide (NO) in bacterial meningitis, concentrations in serum, cerebrospinal fluid (CSF), or both of the precursor (L-arginine) and degradation products of NO (nitrate, nitrite) and tumor necrosis factor (TNF)-alpha were measured in 35 patients and 30 controls. CSF nitrate levels were significantly elevated, mainly due to increased blood-brain barrier permeability, and are therefore not a good parameter for gauging endogenous NO production in the CSF compartment. CSF NO/nitrite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 43 publications
2
42
0
Order By: Relevance
“…53). NOS2 induction, and the subsequent generation of NO, in particular, were argued to contribute to pathology in S. pneumoniae BM (55,87). We found that induction of mRNA for NOS2, but not COX2, was strongly diminished in infected IFN-g gene-deficient animals at both 48 and 72 h p.i.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…53). NOS2 induction, and the subsequent generation of NO, in particular, were argued to contribute to pathology in S. pneumoniae BM (55,87). We found that induction of mRNA for NOS2, but not COX2, was strongly diminished in infected IFN-g gene-deficient animals at both 48 and 72 h p.i.…”
Section: Discussionmentioning
confidence: 69%
“…53). In particular, IFN-g induces NO synthase-2 (NOS2) (54), and increased NO production secondary to NOS2 induction was argued to contribute to pathology during pneumococcal meningitis (55).…”
mentioning
confidence: 99%
“…It has been demonstrated that TNF-␣ can initiate meningeal inflammation (7), resulting in breach of the blood-brain barrier leading to brain edema and increased intracranial pressure (2); and it plays a critical role in neuronal apoptosis in the hippocampus (57). Nitrite levels are usually significantly elevated in CSF of patients with bacterial meningitis and in experimental meningitis (34,58). Inhibition of iNOS has been shown to attenuate alteration of the blood-brain barrier permeability and meningeal inflammation (58).…”
Section: Discussionmentioning
confidence: 99%
“…Once in the subarachnoid space, where the principal humoral and cellular host defense mechanisms are absent (432,555), meningococci proliferate uncontrolled (57). The evolving endotoxin liberation elicits compartmentalized (i.e., confined to the subarachnoid space) activation of proinflammatory cytokines such as TNF, IL-1, IL-6, IL-8, nitric oxide, monocyte colony-stimulating factor, and platelet-activating factor and anti-inflammatory cytokines such as IL-1Ra, IL-10, IL-12, TNFsR-p55, TNFsR-p75, and IL-1sR type II (IL-1sRII) (12,57,192,264,295,429,498,502,517,(519)(520)(521). Among these, TNF and IL-1 enhance the permeability of the blood-brain barrier and promote the influx of neutrophils by upregulation of adherence molecules (258,374,377,428).…”
Section: Pathophysiology Of Meningococcal Meningitismentioning
confidence: 99%